2005
DOI: 10.1128/cdli.12.1.101-106.2005
|View full text |Cite
|
Sign up to set email alerts
|

CD69 Expression on CD4+T Lymphocytes after In Vitro Stimulation with Tuberculin Is an Indicator of Immune Sensitization againstMycobacterium tuberculosisAntigens

Abstract: The expression of the CD69 antigen on CD4 T lymphocytes after in vitro stimulation with purified protein derivative (2 tuberculin units) was used to evaluate the tuberculin reactivities of 52 individuals from four experimental groups: Mycobacterium bovis BCG-vaccinated healthy individuals with a negative tuberculin skin test (TST) result (group A), BCG-vaccinated healthy individuals with a positive TST result (group B), patients with active tuberculosis (TB) before treatment (group C), and individuals with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…PPD or CFP-10 were increased in PTB and TSTþ HHC, compared to TSTÀ Non HHC, supporting that all of these responses differentiate these groups regardless of the stimuli used, and BCG vaccination. These findings are in agreement with immune response against PPD, CFP-10 or ESAT-6 determined by proliferation index [11,27], with IFN-g in cell culture supernatants [4,28], and with the percentages of IFN-g producing CD4 þ and CD8 þ lymphocytes where patients and latent infected individuals are differentiated from non-infected individuals [29,30], unlike the report by Cardoso et al in Brazil, who found that 8/10 TST-controls produced IFN-g in response to ESAT-6 [6].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PPD or CFP-10 were increased in PTB and TSTþ HHC, compared to TSTÀ Non HHC, supporting that all of these responses differentiate these groups regardless of the stimuli used, and BCG vaccination. These findings are in agreement with immune response against PPD, CFP-10 or ESAT-6 determined by proliferation index [11,27], with IFN-g in cell culture supernatants [4,28], and with the percentages of IFN-g producing CD4 þ and CD8 þ lymphocytes where patients and latent infected individuals are differentiated from non-infected individuals [29,30], unlike the report by Cardoso et al in Brazil, who found that 8/10 TST-controls produced IFN-g in response to ESAT-6 [6].…”
Section: Discussionsupporting
confidence: 91%
“…Avgustin et al found an increased expression of CD69 on CD4 þ T lymphocytes stimulated with PPD in BCG-vaccinated TSTþ individuals, in patients with active and treated TB, compared to vaccinated TSTÀ individuals, enabling to differentiate infected individuals from non-infected ones [11]. Our results show that in Figure 3.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Antigen-responsive CD4 + T cells were identified by appearance of activation marker CD69 in the CD3 + CD4 + cell population (Fig. 1E) [29], [30]. In the cohort of TB patients, 30 were defined as new cases and 13 retreatment TB patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…There is a strong correlation between the replication of HIV and the production of proinflammatory cytokines in the lungs of patients with TB (Gold et al, 2004). It has been determined that the cytokine model mRNA could therefore indicate any superiority of Th-2 or the mediated inmmunosupression by the IL-10 ( Westenbrink et al, 2005); and it has been confirmed that immunity towards Mycobacterium is predominantly cellular (Avgustin et al, 2005). Th cells mature from a precursory state Th0 to Th1 phenotype or Th2 (Dovedi et al, 2005).…”
Section: Natural Killer (Nk)mentioning
confidence: 98%